The role of color Doppler in assisted reproduction: A narrative review - Nidhi Sharma; Mahalakshmi Saravanan; Lakshmanan Saravanan MBBS; Sindujhaa Narayanan (Shahid Sadoughi University of Medical Sciences, 2019)
Color Doppler of perifollicular vascularity is a useful assessment tool to predict the growth potential and maturity of Graafian follicles. Power Angio is independent of the angle of insonation and morphometry and provides reliable clues to predict the implantation window of the endometrium. Color Doppler can be used for the prediction of ovarian hyperstimulation syndrome. It can also be used to identify the hyper responder and gonadotropin-resistant type of polycystic ovaries. The secretory scan of corpus luteum can accurately predict its vascularity and functional status. A corpus luteum with decreased blood flow is a very sensitive and specific indicator of threatened and missed abortions. Color Doppler and Power Angio need to be standardized and identical settings should be maintained if different patients, or if changes over time within the same patient are to be compared.